Enterococcus dysbiosis as a mediator of vitamin D deficiency-associated memory impairments - Elizaveta Vinogradova; Zharkyn Jarmukhanov; Madiyar Nurgaziyev; Alibek Kossumov; Ayaulym Nurgozhina; Nurislam Mukhanbetzhanov; Shynggys Sergazy; Laura Chulenabyeva; Argul Issilbayeva; Sholpan Askarova; Aiym Kaiyrlykyzy; Saule Rakhimova; et al. (Heliyon)
Low vitamin D status is linked to disturbance in cognitive performance. This study explored possible ways how composition and functional capacity of the gut microbiome affects vitamin D metabolism, directing serum vitamin D (VitD) levels and memory impairmets. It was found that gut microbiome composition, characterized by an increase in the relative abundance of Enterococcus and correlated with vitamin D deficiency and, as consequence, with memory impairments. A key mechanism identified in the study was the differential utilization of short-chain fatty acids (SCFAs) produced by gut bacteria as substrates for synthesizing vitamin D3 precursor in the skin. This finding confirms a complex interplay between the gut microbiome, host metabolism, and cognitive health, highlighting the potential significance of targeting Enterococcus dysbiosis in future preventive and therapeutic strategies to address VitD deficiency-related memory impairments. These results underscore the importance of understanding and modulating gut microbiome composition to optimize VitD status and cognitive function.